Revealing the Linguistic Features Used in Mantra Pengasihan (The Spell of Affection) in Banyuwangi - Sukarno Sukarno; Wisasongko Wisasongko; Imam Basuki (Pusat Kajian Humaniora FBS Universitas Negeri Padang, 2020)
As a country with full of cultural diversity, Indonesia has various cultures comprising knowledge, belief, art, law, moral, custom, and habit possessed by human as a member of a community. One of the cultural forms in Indonesia is mantra which is still maintained up to the current time and is still practiced by the community in many different places for many different purposes. One of the existing mantras is mantra pengasihan (the spell of affection). The aim of this study is to reveal the role of linguistic features used in mantra pengasihan (MP), especially Sabuk Mangir. The data were collected by deeply interviewing some Subjects (shamans/dukun/pawang or the mantra spellers) and the Object (the target persons) in Glagah and Licin Subdistricts, Banyuwangi. Having been collected, the data were analyzed by content analysis approach to find the types of languages, the narrative elements, the sentence patterns, and the figurative languages used in MP. This research reveals that mostly MP uses (Osing) Javanese and Arabic language, employs opening, main part, and closing elements to express the magic power, chooses declarative and imperative moods to state the physical description of the speller, and the request to the supernatural power, and uses some figurative languages (metaphors, simile, and repetition) to motivate and generate the magical power.Keywords: dukun, magi, mantra, magical power, Osing,